The Effect of Flannel Fabric Busy Book Media on Stimulating Expressive Language Skills of Early Childhood - Nur Rahma; Abdul Saman; Syamsuardi; Rusmayadi; Herlina (Darul Yasin Al Sys, 2026)
Expressive language skills, defined as young children’s capacity to communicate ideas, thoughts, and feelings through spoken words and simple sentences, remain insufficiently stimulated in many Indonesian kindergartens, where instruction continues to rely predominantly on conventional picture-and-explanation media. This study aimed to examine the effect of flannel-fabric Busy Book media on the expressive language skills of children at RA Samasundu, Polewali Mandar Regency, West Sulawesi. A quantitative quasi-experimental approach with a nonequivalent control group design was employed, involving 30 Group B children aged 5–6 years who were selected through saturated sampling and assigned to an experimental group using flannel-fabric Busy Book media (n = 15) and a control group using conventional picture-based media (n = 15). Data were collected using a six-indicator observation sheet based on a four-level developmental scale and analyzed through descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, paired-samples t-tests, and independent-samples t-tests. The control group’s mean score increased only marginally from 13.47 at pretest to 13.73 at posttest, with no statistically significant difference, t(14) = −0.673, p = .512. In contrast, the experimental group’s mean score increased from 14.00 to 20.53, representing a statistically significant improvement, t(14) = −11.678, p < .001. Posttest scores also differed significantly between the experimental and control groups, t(28) = −12.448, p < .001, with a mean difference of 6.80. Moreover, the experimental group’s gain score (M = 6.80) was significantly higher than that of the control group (M = 1.67), t(28) = 10.548, p < .001. These findings demonstrate that flannel-fabric Busy Book media is more effective than conventional picture-based media in stimulating early childhood expressive language skills because its concrete, manipulable, and multisensory features encourage active verbal engagement. The study contributes empirical support for constructivist and sociocultural perspectives on early language development and provides teachers with a practical and affordable instructional medium. However, the small single-site sample and brief intervention period limit the generalizability of the findings, warranting further research with larger samples, longer interventions, and comparisons involving alternative instructional media.